The Effect of Capital Expenditure, Balancing Funds, Regional Original Revenue and E-Government on Local Government Financial Performance - SUTISMAN, Entar; PRASETIANINGRUM, Septyana; SUTISNA, Entis; NOY, Ismail R.; DARMAYANTI, Novi; FAHREZA, Ellycia Rahma Nurfidya (PT Keberlanjutan Strategis Indonesia, 2024)
This study examines the effect of capital expenditure, balancing funds, local revenue, and e-government on the financial performance of local governments (Study on local governments in East Java in 2020-2022). The research approach used in this study is quantitative, using secondary data. The population in this study was local governments in East Java for 3 consecutive years for the period 2020-2022. The sampling technique used was purposive sampling, and 114 samples were obtained from 38 districts and cities in East Java. The data analysis techniques used were inner model analysis, outer model analysis, and hypothesis testing. The results of this study indicate that partially, the Capital Expenditure Variable has a negative effect on the financial performance of local governments, the Balancing Fund has a positive effect on the financial performance of local governments, Local Revenue has a positive effect on the financial performance of local governments, and E-Government has a negative effect on the financial performance of local governments.